Analyzing the Impact of Learning Styles and Preferences on Vocational English Education Using Multiple Linear Regression Model - Zhang, Yamei (Proceedings of the ... IEEE International Conference on Knowledge Innovation and Invention (Online), 2023)
Students' learning styles and preferences significantly impact their learning outcomes. Thus, the influence of students' learning styles and preferences on vocational English education was analyzed using a mathematical model. Having 50 students as research subjects, it was investigated how learning styles and preferences affected academic performance. Data were collected on learning styles, preferences, and academic achievements to analyze the data using multiple linear regression. The results indicated that students' visual and auditory learning styles substantially impacted their academic performances, while text and video preferences showed less significant influence. Therefore, teachers need to tailor personalized teaching strategies based on student's learning styles and preferences to enhance learning outcomes. This study result offered valuable insights into vocational English education and proposed the implementation of personalized teaching methods.